ANALISIS PERBANDINGAN PERLINDUNGAN HUKUM TERHADAP MEREK DI INDONESIA DAN KOREA SELATAN - Ruhtiani, Maya (LPPM Universitas Harapan Bangsa, 2024)
Along with globalization, intellectual property has become a valuable asset that requires solid legal protection in various countries in an effort to improve the economy, including the legal protection of trademarks. This article analyses the legal protection of trademarks by comparing the legal arrangements between Indonesia and South Korea. Normative legal research is used to explore issues related to trademarks by using a statute approach and comparative approach and secondary data as the primary data. The results of the research and discussion show that trademark protection in Indonesia and South Korea have many similarities in terms of registration procedures, duration of protection, and dispute resolution mechanisms. However, there are differences in aspects such as statutory arrangements, management bodies, sanctions for violations, and some technical details of trademark registration between the two countries. The conclusion of this study is that the legal protection system between Indonesia and South Korea apply first to the file system. However, South Korea technically still recognizes the existence of a trademark that is used but has not been registered and can be protected by the provisions of business competition legislation. At the same time, in Indonesia, the opportunity has yet to be regulated at all because all trademarks must go through registration first to obtain legal protection as stipulated in the Trademark Act and Geographical Indications.